Kajian Literatur: Tinjauan Sistem Manajemen Laboratorium IPA di SD, SMP, dan SMA - Salma Samputri (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2025)
This study aims to examine laboratory management systems across primary and secondary education levels in Indonesia—namely elementary (SD), junior high (SMP), and senior high schools (SMA)—with a focus on practices, challenges, and improvement strategies. The research method employed is a literature review, analyzing 30 relevant national journals, consisting of 10 for each educational level. The findings reveal that the application of management functions (planning, organizing, actuating, and controlling) varies across levels and depends on available resources. At the elementary level, laboratory management remains basic and is often undocumented. In junior high schools, formal structures begin to develop, yet they are hampered by the lack of technical personnel and inadequate facilities. Senior high schools exhibit more structured and complex management systems, though still challenged by insufficient evaluation mechanisms and staff training. The study concludes that effective laboratory management requires ongoing teacher training, supportive policies, and the integration of technology to ensure safety, efficiency, and quality in science education. Recommendations include enhancing teacher capacity, recruiting professional laboratory technicians, and establishing SOPs based on national education standards.